Respuesta :

hello
by identity : a²-b² = (a-b)(a+b)
m²-25 = m²-5² (m-5)(m+5)

An expression that is equivalent to the considered expression is [tex](m+5)(m-5)[/tex]

What is the product result of (a+b)(a-b) ?

Suppose two numbers are there as 'a' and 'b'.

Then, we get:

[tex](a+b)(a-b) = a(a-b) + b(a-b) = a^2 -ab + ab - b^2 = a^2 - b^2\\(a+b)(a-b) = a^2 - b^2[/tex]

What are equivalent expressions?

Those expressions who might look different but their simplified forms are same expressions are called equivalent expressions.

To derive equivalent expressions of some expression, we can either make it look more complex or simple.

For this case, we have the given expression as:

[tex]m^2 - 25[/tex]

We can rewrite 25 as square of 5

Thus, we get:

[tex]m^2 - 25 =m^2 - 5^2[/tex] (this itself is one of the equivalent form of the original equation, but let we make it more different than the original one)

Now, since we know that: [tex](a+b)(a-b) = a^2 - b^2[/tex] thus, we can rewrite the obtained expression as:

[tex]m^2 - 5^2 = (m+5)(m-5)[/tex]

Thus, an expression that is equivalent to the considered expression is [tex](m+5)(m-5)[/tex]

Learn more about equivalent expressions here:

https://brainly.com/question/26413706